2022
DOI: 10.2196/35336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Collaborative Care Program for Patients With Treatment-Resistant Schizophrenia: Protocol for a Multiple Case Study

Abstract: Background Approximately one-third of all patients with schizophrenia are treatment resistant. Worldwide, undertreatment with clozapine and other effective treatment options exist for people with treatment-resistant schizophrenia (TRS). In this respect, it appears that regular health care models do not optimally fit this patient group. The Collaborative Care (CC) model has proven to be effective for patients with severe mental illness, both in primary care and in specialized mental health care faci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The impact of psychological interventions on improving patients has been confirmed by a large number of studies with very precise effects [ 30 ]. Some studies on psychological interventions for patients with somatic disorders have shown improved quality of life in patients who received psychological interventions [ 31 ]. For patients with psychiatric disorders, psychological interventions can also improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of psychological interventions on improving patients has been confirmed by a large number of studies with very precise effects [ 30 ]. Some studies on psychological interventions for patients with somatic disorders have shown improved quality of life in patients who received psychological interventions [ 31 ]. For patients with psychiatric disorders, psychological interventions can also improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine mungkin merupakan satu-satunya antipsikotik yang efektif untuk menekan perilaku agresif. Penting untuk mengidentifikasi populasi schizophrenia yang rentan dan memberikan pengobatan serta perawatan yang efisien (10) Perawatan kesehatan mental yang harusnya disarankan untuk memberikan intervensi awal manajemen penyakit anti-stigma (14),( 15),( 17), (18) dan psikoedukasi keluarga kepada orang yang didiagnosis schizophrenia dan pengasuh keluarga mereka, membantu mereka mengembangkan pemahaman optimis tentang konsep schizophrenia dan mengurangi konsekuensi negatif stigma publik dan internal (16), (18) . Sangat penting juga bagi pengelola kesehatan jiwa di fasilitas kesehatan tingkat pertama untuk lebih berperan dalam melakukan kontrol dalam hal perawatan dan terapi kolaboratif.…”
Section: Dibagianunclassified
“…Re-admission of schizophrenic patients to mental health services for less than one day has become a popular issue for intervention from both service providers, families as part of the closest unit of sufferers and needs attention from the community. There are various factors that cause the return of schizophrenic patient to be re-admitted in mental health services, such as unmarried status, previous history of forced entry, longer forced entry days, and shorter total days of admission, which were associated with an increased risk for one year re-enrollment [9]- [11]. The impacts of re-admission include; increased cost of care, longer treatment, increased burden on family and clients, decreased quality of life and cognitive, and disease severity.…”
Section: Introductionmentioning
confidence: 99%